2010
DOI: 10.1007/s00221-010-2291-6
|View full text |Cite
|
Sign up to set email alerts
|

Cortical processing of facial tactile stimuli in temporomandibular disorder as revealed by magnetoencephalography

Abstract: We used magnetoencephalography (MEG) to investigate the cortical processing of an innocuous facial tactile stimulus in healthy subjects and in a group of subjects suVering from chronic temporomandibular disorder (TMD). Equivalent current dipoles (ECDs) were extracted for a time period of 1 s following stimulus application, and their location, duration and onset time determined. The counts of ECDs extracted did not diVer signiWcantly between the two groups. In contrast, we found statistically signiWcant diVeren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 68 publications
2
12
0
1
Order By: Relevance
“…Furthermore, magnetoencephalography was performed in TMD patients and demonstrated evidence of altered brain responses to innocuous tactile stimulation above the masseter muscle compared to healthy controls. 101 These findings support the presence of abnormal central pain processing in TMD.…”
Section: Proposed Pathophysiologic Mechanismssupporting
confidence: 59%
“…Furthermore, magnetoencephalography was performed in TMD patients and demonstrated evidence of altered brain responses to innocuous tactile stimulation above the masseter muscle compared to healthy controls. 101 These findings support the presence of abnormal central pain processing in TMD.…”
Section: Proposed Pathophysiologic Mechanismssupporting
confidence: 59%
“…These effects encompassed parietal areas (tentatively, first [area c in Fig. 6] and second somatosensory cortex [area b]), known to be involved in pain (Alonso et al, 2010, Mazzola et al, 2012). The preponderance of left hemispheric involvement in this study (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The greater temporal acuity of MEG revealed that the evoked responses in TMD, termed equivalent current dipoles, had earlier onset times, were longer in duration, were less tightly grouped, and had different distribution of response power over the 1s response time [134]. …”
Section: Neuroimaging Of Brain Activity Evoked By Non-painful Stimulamentioning
confidence: 99%